Incidence of Ascites in Canines: Analysis and Prospective Study - Baria, Vinay; Vagh, Arshi A; Bilwal, Avinash K; Parmar, Vijay L; Sherasiya, Raisudin M; Patel, Priyanshi V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A detailed study from April 2022 to March 2023 conducted at the Veterinary Clinical Complex, Kamdhenu University, Junagadh, Gujarat. The study involved examination of 1532 dogs for various clinical conditions. Among them, 61 dogs (3.98%) exhibited ascites which was confirmed through different diagnostic methods. The study revealed a higher incidence of ascites in Labrador retrievers (37.70%) and dogs between 1 to 5 years of age (54.10%). Additionally, female dogs showed a higher incidence (62.30%) than males, with the month of May showing the highest occurrence (11.48%).
Keywords: Age; Breed; Ascites; Gender; Incidence; Labrador retriever